A ideia de cinema científico presente na obra de Jean Painlevé - Biava, Pedro (2015)
Jean Painlevé s (1902-1989) scientific cinema is filled with elements that turned his analysis into an important source to study the relation between Art and Science during the first decades of the 20th century, especially in France. The filmmaker s work is composed of more than 200 movies, performed throughout more than six decades of work as a filmmaker, scientist and Science propagator. Painlevé used cinema as a research and scientific propagation instrument, and he used a particular mixture of technical and narrative resources to perform his work. He connected surrealist art to scientific objectivity, always seeking to show the spectator his own enchantment for scientific research. Some of his films became a reference for the Science documentarians that followed him. It is the case of The Seahorse (1934), his most popular film. It gathers images that were never seen before about the birth of babies from this species, where the male has the role of giving birth offspring. Painlevé used a narrative that mixed technical and scientific information along with dramatic and comical elements. It s possible to notice how his work helped Science become more accessible and popular. His work had Marine Biology as a main theme, but he worked with other scientific themes that interested him in Physics, Chemistry and other areas. Using cinema as a source of science history research is not only a tool that allows an analysis of the technical evolution of image capturing, but it´s also a sociocultural understanding of the historical context in which the cinematographic technique was used. Analyzing the films as part of the documents studied in the research was essential in the process. Besides an extensive filmography, Painlevé left a series of written material talking about cinema, which helped understand his vision of Science, and the role he assigned to cinema in the context of scientific development. In this dissertation, the objective was to cross information presented in these films and texts to understand the aspects of Science History in his work